Immunologic features of asymptomatic postvaccination infections with the Delta variant of SARS‐CoV‐2 in adults - Rui Duan; Qiang Mao; Xu Ding; Qiwu Qiu; Pei Wang (Immunity, Inflammation and Disease, 2022)
Abstract Background Asymptomatic infections may play an important role in severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) Delta variant transmissions. However, the immunologic features of asymptomatic postvaccination infections with the Delta variant of SARS‐CoV‐2 in adults remain to be defined. Methods A retrospective study involving 36 vaccinated adults infected with the SARS‐CoV‐2 Delta variant was performed. Their demographic and laboratory data were collected and analyzed in The First People's Hospital of Jingmen from August 4 to 20, 2021. Results Of the 36 adults, 6 persons had an asymptomatic infection. The severity of the SARS‐CoV‐2 infections was highly correlated with the doses of vaccinations (p = 0.019). The symptomatic and asymptomatic infected SARS‐CoV‐2 adults showed normal levels of leukocytes and lymphocytes. The C‐reactive protein (CRP) and interleukin‐6 (IL‐6) levels were elevated in the symptomatic groups. The period between the last vaccination to the time of infection in the asymptomatic group was longer than that in the mild and moderate groups (73 vs. 61 vs. 50 days; p = 0.047). The percentage of suppressor T‐cells in the asymptomatic group was the highest (32.2 ± 4.0% vs. 22.0 ± 7.2% vs. 29.3 ± 8.0%; p = 0.004). The signal‐to‐cutoff ratio value of total antibody against SARS‐CoV‐2 in the asymptomatic group was lower than that in the other two groups (383 vs. 703 vs. 1792; p < 0.001) and much lower than that in the moderate group. The multivariate ordinal logistic analysis after adjusting for gender, vaccination date, and vaccination dose indicated that CRP at Days 4−7 and 8−14, IL‐6 on Days 4−7, and total antibody were risk factors for coronavirus disease 2019 severity. Conclusions Asymptomatic postvaccination infections with the Delta variant of SARS‐CoV‐2 in adults tend to infect persons vaccinated twice. The immunophenotype profile for asymptomatic postvaccination infections is less inflammatory and accompanied by relatively lower antibody titers.